2013
DOI: 10.1111/jhn.12059
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sociocultural factors on the eating attitudes of Lebanese and Cypriot students: a cross‐cultural study

Abstract: The aim of this comparative cross‐cultural study was to explore the relationship between eating behavior and sociocultural attitudes towards appearance and body image in female university students from two distinct cultural contexts, Cyprus and Lebanon. The Dutch Eating Behavior questionnaire (DEBQ) and the Perceived Sociocultural Influences on Body Image and Body Change Questionnaire were used to assess the different variables in 200 students from each culture. Results indicated that the Lebanese students eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Katsounari and Zeeni found that Cypriot female university students were preoccupied with their weight by trying to gain, lose, or maintain it. In addition, sociocultural influences such as the importance of the opinion of one's mother, male friend and female friend were found to be predictors of disordered eating behavior in Cypriot female students . Furthermore, the levels of disordered eating in Cyprus seem to be higher than most countries assessed in the literature.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Katsounari and Zeeni found that Cypriot female university students were preoccupied with their weight by trying to gain, lose, or maintain it. In addition, sociocultural influences such as the importance of the opinion of one's mother, male friend and female friend were found to be predictors of disordered eating behavior in Cypriot female students . Furthermore, the levels of disordered eating in Cyprus seem to be higher than most countries assessed in the literature.…”
Section: Introductionmentioning
confidence: 75%
“…In addition, sociocultural influences such as the importance of the opinion of one's mother, male friend and female friend were found to be predictors of disordered eating behavior in Cypriot female students. 13 Furthermore, the levels of disordered eating in Cyprus seem to be higher than most countries assessed in the literature. Specifically, a study conducted by Hadjigeorgiou, Tornaritis, Savva, Solea, and Kafatos, 14 who conducted a 6year follow-up (2003 and 2010) in a large sample of Greek-Cypriot adolescents, revealed that 18.8% of males and 34.4% of females in 2003 and 18.8% of males and 35.9% of females in 2010 had significant disordered eating attitudes and behaviors (Eating Attitudes Test-26 [EAT-26] score higher than 20).…”
Section: Introductionmentioning
confidence: 86%
“…The DEBQ has been administered in Lebanon to a sample of 398 female undergraduates aged 17–25. The scale showed excellent internal consistency for restrained eating ( α = .93), external eating ( α = .82), and emotional eating ( α = .95) (Zeeni et al., ). In the current study, the Cronbach's alphas of the three subscales were .91, .83, and .92 for restrained, external, and emotional eating, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Social connections are vital in a Lebanese context; however, a strong family connection is the most important social structure (Zeeni et al 2013). This was highlighted in the literature as to its effects in overcoming the effects of the war in Lebanon (Farhood 1999).…”
Section: Sociocultural Contextmentioning
confidence: 99%